2014
DOI: 10.1007/s10029-014-1214-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective observational study on the incidence of incisional hernias after colorectal carcinoma resection with follow-up CT scan

Abstract: CT follow-up can identify significantly more IH than clinical examination alone, in particular if the radiologist focuses on IH development. Furthermore, we showed that focused CT evaluation diagnosed IH 7 months earlier than routine CT and 5 months earlier than clinical follow-up alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 10 publications
2
37
0
Order By: Relevance
“…The incidence of incisional hernias after LAR for rectal cancer in our department is high, with 45.1 % after 1.9 years. This is in line with other studies with equal follow-up time and methodology [11,12]. Pereira et al found an incidence of almost 40 % with CT follow-up [11] and we previously reported the incidence of incisional hernias after resection of colorectal carcinoma to be 35 % with a methodology similar to the present study [12].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The incidence of incisional hernias after LAR for rectal cancer in our department is high, with 45.1 % after 1.9 years. This is in line with other studies with equal follow-up time and methodology [11,12]. Pereira et al found an incidence of almost 40 % with CT follow-up [11] and we previously reported the incidence of incisional hernias after resection of colorectal carcinoma to be 35 % with a methodology similar to the present study [12].…”
Section: Discussionsupporting
confidence: 95%
“…This is in line with other studies with equal follow-up time and methodology [11,12]. Pereira et al found an incidence of almost 40 % with CT follow-up [11] and we previously reported the incidence of incisional hernias after resection of colorectal carcinoma to be 35 % with a methodology similar to the present study [12]. CT At that time the abdomen was closed with a running loop suture of poly-dioxanone 1 without any consideration on the suture to wound length ratio (SL/WL) or on the size of the tissue bites during the closure.…”
Section: Discussionsupporting
confidence: 93%
“…The PRISMA flow diagram is shown in addendum 3 (Key Question A). Fifteen records were included in the qualitative analysis [3][4][5][6][50][51][52][53][54][55][56][57][58][59][60]. Only four studies were retained as High Quality and are listed in the Summary of Findings table (Table 2) [5, [50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…Incisional hernias are a frequent complication of abdominal wall incisions, but a wide range of incisional hernia rates are reported [1][2][3][4][5][6]. The weighted mean incisional hernia rate at 23.8 months was 12.8 % in a systematic review and metaregression study [7], but incidence rates up to 69 % have been reported in high-risk patients with prospective longterm follow-up [8].…”
Section: Introductionmentioning
confidence: 99%
“…Incisional hernia is a common complication following both stoma trephine and laparotomy for colorectal resection . Resultant pain, obstruction and impaired mobility are all indications for surgical repair, which is often performed by colorectal surgeons.…”
mentioning
confidence: 99%